Implementasi Metode Waterfall dalam Pengembangan Sistem Point of Sales dan e-Commerce - Desi Ramayanti; Yuwan Jumaryadi; Aris Sunandar; Kolidi Kolidi (TIN: Terapan Informatika Nusantara, 2023)
Along with the development of technology, Micro, Small and Medium Enterprises need to adapt to technology in order to compete and also expand the market reach of selling their products. As for Micro, Small and Medium Enterprises, which still use manual methods in marketing their products, it is an obstacle in developing their business in the current digitalization era because of the difficulty in carrying out promotions and marketing. In today's digital era, E-Commerce applications are a solution for MSMEs to increase efficiency and effectiveness in their business. In developing the system carried out using the waterfall methodology. The waterfall methodology consists of communication, planning, modeling, construction, and implementation. Meanwhile, application design modeling uses Hyper Text Markup Language, Cascading Style Sheets, and Semantic UI to create an attractive appearance and is easy for users to use, and the Angular Framework which uses Typescript as its programming language and Firebase as a database. After the system is developed, it will be tested using black box testing. The system developed is able to provide easy access via the internet network, as well as increase the efficiency and effectiveness of product promotion and marketing processes and make it easier for store owners to view product sales report data